QUALITY OF LIFE FOLLOWING CANCER TREATMENT - Ara Islam, Ferdous (European Scientific Journal, ESJ, 2014)
This cross sectional study was carried out among 301 cancer patients attending Dhaka Medical College Hospital, Bangladesh in the Department of Radiotherapy to observe the quality of life following cancer treatment.A semi structured questionnaire was used to collect the data. The quality of life (QOL) in case of pain, ability to self care,able to play role activity in family & society can take part in family and leisure activities were improved. Whereas in case of loss of household asset the situation was worsen. The best scores improved in the different indicators before & after Radiotherapy such as: pain from 27.77% to 30.15%, ability to self care 75.39% to 84.12%, ability to play role activity in family & society 69.84% to 75.39%, can take part in family and leisure activities 74.60% to 79.36%. The Best scores for Chemotherapy: pain from 23.0% to 30.24% ability to self care from 61.97% to 77.46%, ability to play role activity in family & society 63.38% to 74.64%, can take part in family and leisure activities 63.38% to 69.01% and the Best scores for both Radiotherapy & Chemotherapy were improved in the same way. However, the Best scores deteriorated in case of Radiotherapy were 84.61% to 89.42%, Chemotherapy 70.42 % to 42.25% and for both Radiotherapy & Chemotherapy 84.61% to 89.42% for loss of household asset. The quality of life (QOL) of the respondents improved following treatment but at the same time they lost their household asset. The Best scores for quality of life improved following Radiotherapy, Chemotherapy and combined therapy (Radiotherapy and Chemotherapy) which was significant. With relation to loss of household assets the best scores deteriorated in all the three groups of treatment which was also found significant.